PENGEMBANGAN KUALITAS SUMBER DAYA MANUSIA MELALUI PROGRAM INSERVICE TRAININGDI SMK ANNUR FATMAH TRAWAS MOJOKERTO - Satunggale Kurniawan; Miftakul Sania; Muhammad Afifi Rahman (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
Low human resources in schools is a problem that often occurs, causing a major impact on the quality of education implementation. To overcome this, it is necessary to develop human resources through in-service training programs which are the right and effective solution to overcome this problem. This research aims to reveal the challenges and opportunities as well as strategies in developing human resources at Annur Fatmah Trawas Vocational School, Mojokerto. This research uses a qualitative approach with data collection techniques through interviews, documentation and observation. The data sources used were school principals, teaching staff and educational staff at Annur Fatmah Trawas Vocational School, Mojokerto. The research results show that there are challenges faced in implementing inservice training such as lack of motivation, limited time, and lack of preparation. However, there are also opportunities that can be utilized, such as support from superiors, competent presenters and supporting facilities. Apart from participating in training at school, teaching and education staff also carry out informal self-development. The human resource development process through the inservice training program is carried out in several steps, namely identifying needs, program design, program implementation and evaluation. In this way, teaching and education staff experience benefits such as increasing insight, abilities, skills, and increasing adaptability. So that the inservice training program provides real benefits, which have an important role in improving the quality of education.